Metamizole/dipyrone for the relief of cancer pain: A systematic review and evidence-based recommendations for clinical practice. (January 2017) - Gaertner, Jan; Stamer, Ulrike M; Remi, Constanze; Voltz, Raymond; Bausewein, Claudia; Sabatowski, Rainer; Wirz, Stefan; Müller-Mundt, Gabriele; Simon, Steffen T; Pralong, Anne; Nauck, Friedemann; Follmann, Markus; et al.
Background: Dipyrone (metamizole) is one of the most widely used non-opioid analgesics for the treatment of cancer pain. Aim: Because evidence-based recommendations are not yet available, a systematic review was conducted for the German Guideline Program in Oncology to provide recommendations for the use of dipyrone in cancer pain. Design: First, a systematic review for clinical trials assessing dipyrone in adult patients with cancer pain was conducted. Endpoints were pain intensity, opioid-sparing effects, safety, and quality of life. Data sources: The search was performed in MedLine, Embase (via Ovid), and the Cochrane Library (1948–2013) and additional hand search was conducted. Finally, recommendations were developed and agreed in a formal structured consensus process by 53 representatives of scientific medical societies and 49 experts. Results: Of 177 retrieved studies, 4 could be included (3 randomized controlled trials and 1 cohort study, n  = 252 patients): dipyrone significantly decreased pain intensity compared to placebo, even if low doses (1.5–2 g/day) were used. Higher doses (3 × 2 g/day) were more effective than low doses (3 × 1 g/day), but equally effective as 60 mg oral morphine/day. Pain reduction of dipyrone and non-steroidal anti-inflammatory drugs did not differ significantly. Compared to placebo, non-steroidal anti-inflammatory drugs, and morphine, the incidence of adverse effects was not increased. Conclusion: Dipyrone can be recommended for the treatment of cancer pain as an alternative to other non-opioids either alone or in combination with opioids. It can be preferred over non-steroidal anti-inflammatory drugs due to the presumably favorable side effect profile in long-term use, but comparative studies are not available for long-term use.